2019
DOI: 10.2217/pmt-2018-0087
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Interdisciplinary Intensive Outpatient Programs in a Population With Diverse Chronic Pain Conditions: A Systematic Review and Meta-Analysis

Abstract: Aim: To explore the overall effectiveness of interdisciplinary intensive outpatient treatment programs in adults with chronic pain. The secondary aim was to examine the effect of the intervention on individual outcome measures including pain intensity, pain catastrophizing, depressive symptoms, quality of life and describe its effect on medication use. Methods: The preferred reporting items for systematic review and meta-analysis protocols reporting guidelines were followed in this systematic review and meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…This program and similar interdisciplinary programs 36 have engaged patients in intensive, daily, several week periods of care which is not a paradigm that can realistically be made available to all persons with chronic pain and co-occurring disorders. 37 A recent study examined three care paradigms offering different intensities of rehabilitative care for chronic low back pain and found that all reduced work sick leave taken in the ensuing 12 months and that there were no differences in quality of life, sociability or personal beliefs between patients completing the different treatment intensities. Intensive residential care is not a realistic model for all patients, 38 given the high costs to individuals and/or third parties.…”
Section: Discussionmentioning
confidence: 99%
“…This program and similar interdisciplinary programs 36 have engaged patients in intensive, daily, several week periods of care which is not a paradigm that can realistically be made available to all persons with chronic pain and co-occurring disorders. 37 A recent study examined three care paradigms offering different intensities of rehabilitative care for chronic low back pain and found that all reduced work sick leave taken in the ensuing 12 months and that there were no differences in quality of life, sociability or personal beliefs between patients completing the different treatment intensities. Intensive residential care is not a realistic model for all patients, 38 given the high costs to individuals and/or third parties.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses have established pain rehabilitation programs as an effective treatment option for reducing chronic pain and associated disability (Bujak, Regan, Beattie, & Harrington, 2019; Kamper et al, 2015; Semrau et al, 2015). Multidisciplinary pain management programs were available as early as the 1950s, when Dr. John J. Bonica opened the first multidisciplinary pain clinic to improve functional outcomes for patients with chronic pain (Tompkins, Hobelmann, & Compton, 2017).…”
Section: Pain Rehabilitation Programsmentioning
confidence: 99%
“…A growing body of literature continues to demonstrate that pain rehabilitation programs improve physical functioning, pain severity, and mood among patients with chronic pain (Bailey, Kurklinsky, Sletten, & Osborne, 2018; Hooten, Townsend, Sletten, Bruce, & Rome, 2007), along with a significant reduction in medical costs (Sletten, Kurklinsky, Chinburapa, & Ghazi, 2015). A recent systematic review of a total of 3,370 patients found that interdisciplinary, intensive outpatient pain rehabilitation programs contributed to clinical improvements in pain, mood, pain catastrophizing, and QOL, with large effect sizes (Bujak et al, 2019). Impressively, there is even evidence that improvements in functioning are sustained up to 13 years later (Patrick, Altmaier, & Found, 2004).…”
Section: Pain Rehabilitation Programsmentioning
confidence: 99%
“…Although healthcare practice in Malaysia has improved over the previous decades, it is predominated by hierarchy working and working in-silo culture [ 15 , 16 ]. Hence, working with various disciplines was found to have a positive impact on clients in a holistic manner which is beyond than just related to the condition [ 17 , 18 ]; for example, chronic pain clients not only received management on the pain but also had a better outcome on physical functions, mental health, emotion, and social and quality of life. Healthcare practitioners need to acknowledge the role of each other for the benefit of the client.…”
Section: Introductionmentioning
confidence: 99%